Stability of neutral functional differential equations in terms of measures - Bena, M. A.; Dos Reis, J. G.; Santos, J. S. (Watam Press, 1999)
In this paper we investigate the relationships between different concepts of stability in measure for the solutions of an autonomous or periodic neutral functional differential equation.